IDC theory: habit and the habit loop - Chen, Wenli; Chan, Tak Wai; Wong, Lung Hsiang; Looi, Chee Kit; Liao, Calvin C. Y.; Cheng, Hercy N. H.; Wong, Su Luan; Mason, Jon; So, Hyo Jeong; Murthy, Sahana; Gu, Xiaoqing; Pi, Zhongling (Springer, 2020)
Interest-driven creator (IDC) theory is a design theory that intends to inform the design of future education in Asia. It consists of three anchored concepts, namely, interest, creation, and habit. This paper presents the third anchored concept habit as well as the habit loop. IDC theory assumes that learners, when driven by interest, can be engaged in knowledge creation. Furthermore, by repeating such process in their daily learning routines, learners will form interest-driven creation habits. The habit loop, the process of building such a habit, consists of three component concepts— cuing environment, routine, and harmony. The cuing environment is a habit trigger that tells the students’ brain to get prepared and go into an automatic mode, letting learning behavior unfold. Routine refers to the behavioral patterns the students repeat most often, literally etched into their neural pathways. Harmony refers to the affective outcome of the routine activity as well as the integration or stabilization of habits; that is, through the routine behavior and action, students may feel that their needs get fulfilled, feel satisfied, and experience inner peace. It is our hope that such habitual behavior of creating knowledge can be sustained so long that students ultimately become lifelong interest-driven creators. This paper focuses on the description of the three components of the habit loop and discusses how these components are related to the interest loop and the creation loop in supporting learners in developing their interest-driven creation capability.